Performance Analysis of D2D Communication over LTE-A Network with Mode Switching - Esfandiar, Ali (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
In recent years, the global trend in mobile and smart devices with a wide range of multimedia application led to the rapid growth of data traffic in the cellular networks. Long Term Evolution - Advanced (LTE-A) as the enhanced mobile communication standard carries on a huge part of this requirement. In order to balance the uploading traffic from LTE-A, 3rd Generation Partnership Project (3GPP) introduced Deviceto- Device (D2D) communication over LTE-A in its release 12. D2D communication enables users to send data packets to the receiver through a direct link which is called Side Link (SL) or users are able to communicate through the base station which is called Relay Path (RP). The communication can be switched between SL and RP during the communication by the base station. This switching between links is called Mode Switching (MS). This thesis is attentive in measuring Quality of Service (QoS) in D2D and RP communications over LTE-A network using Voice over IP (VoIP) application. In order to simulate various conditions and different location distribution in the network, four scenarios are simulated in OMNET++. The examined performance results illustrate that D2D communication performs very well in short distances and also, by increasing distance between two mobiles, communication needs to change its path from the SL to the RP. In addition, this dissertation demonstrates how employing MS in a suitable state can improve the QoS of communication in LTE-A and utilize advantages of both D2D and RP communications.

ÖZ: Son yıllarda, geniş bir multimedya uygulamasına sahip mobil ve akıllı cihazlardaki küresel eğilim, hücresel ağlarda veri trafiğinin hızlı bir şekilde artmasına neden olmuştur. Uzun Süreli Evrim - Gelişmiş mobil iletişim standardı olan Gelişmiş (LTE-A) bu gereksinimin büyük bir bölümünü taşıyor. Yükleme trafiğini LTE-A'dan dengelemek için, 3. Nesil Ortaklık Projesi (3GPP), piyasaya sürülmesi sırasında LTE-A üzerinden Cihazdan Cihaza (D2D) haberleşmeyi başlattı. Side Link (SL) veya kullanıcılar olarak adlandırılan bir doğrudan bağlantı, kullanıcılar, Röle Yolu (RP) adı verilen baz istasyonu üzerinden iletişim kurabilir. İletişim, baz istasyonu tarafından iletişim sırasında SL ve RP arasında değiştirilebilir. Bu bağlantılar arasında geçiş yapmak Mod Değiştirme (MS) olarak adlandırılır. Bu tez, D2D'deki Servis Kalitesinin (QoS) ve IP üzerinden Ses (VoIP) uygulamasını kullanarak LTE-A ağı üzerinden RP iletişiminin ölçülmesinde özenlidir. Ağdaki çeşitli koşulları ve farklı konum dağılımını simüle etmek için OMNET ++ 'da dört senaryo simüle edilmiştir. İncelenen performans sonuçları, D2D iletişiminin kısa mesafelerde çok iyi performans gösterdiğini ve ayrıca iki cep telefonu arasındaki mesafeyi artırarak, iletişimin SL'den RP'ye olan yolunu değiştirmesi gerektiğini göstermektedir. Ek olarak, bu tez, MS'in uygun bir durumda kullanılmasının, LTEA'da QoS iletişimini nasıl geliştirebileceğini ve hem D2D hem de RP iletişim avantajlarını nasıl kullanabileceğini göstermektedir.
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2019. Supervisor: Assoc. Prof. Dr. Gürcü Öz
Keywords: Computer Engineering; Mobile communication systems; LTE-A; D2D; QoS; VoIP; MS; SL; RP